"Flying over the crisis": A study on interdisciplinary metaphors of resilience. (March 2023) - Kriegsmann-Rabe, Lisa Milena; Hiebel, Nina; Maus, Katja; Geiser, Franziska
Background/Aim: Metaphors on theoretical concepts may be congruent or divergent from their explicit definitions. We carried out a secondary qualitative analysis on metaphors of members of an interdisciplinary research group on resilience and investigated: (A) Which metaphors do experts in different disciplines use to describe people showing resilience? (B) Do these (implicit) metaphors support the (explicit) theses of the research group on resilience? (C) Do we find differences between experts from different disciplines in the use of metaphors on resilience?Method: Nine guideline-based interviews with experts from medicine, psychology, philosophy, and theology were studied using a systematic metaphor analysis, basing on inductive and deductive categorizations.Results: Eight metaphor sources were identified, for example, battle, path . Experts used similar metaphors to describe resilience that often overarched the concepts of resilience as a trait, process, and outcome. Moments of vulnerability within the resilience trajectory were found.Conclusions: The analysis revealed high concordance of metaphors across different disciplines, reflecting both the ideas of the group as well as the mainstream view of resilience. This supports that implicit concepts may be more difficult to reframe than explicit theories. Few differences between disciplines may point to the impact of an overarching Western concept of individual resilience.